DIFFERENTIAL MUELLER-MATRIX MAPPING OF THE POLYCRYSTALLINE COMPONENT OF BIOLOGICAL TISSUES OF HUMAN ORGANS - Padure, Andrei; Bakun, Oksana; Mikirin, Ivan; Dubolazov, Oleksandr; Soltys, Iryna; Olar, Oleksandr; Ushenko, Yuriy; Ushenko, Oleksandr; Palii, Irina; Kumargazhanova, Saule (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
The article presents the materials of diagnostic application of the method of differential Mueller-matrix mapping of optically anisotropic architectonics of the layers of soft matter of the female reproductive sphere – histological sections of uterine biopsy. The efficiency and accuracy of differential diagnostics of benign and precancerous conditions of endometrial tissue are considered using statistical analysis of algorithmically reproduced maps of average values of linear and circular birefringence and dichroism parameters of optically anisotropic architectonics of representative samples of native histological sections of the uterine wall. The values of the balanced accuracy of differential diagnostics are presented by using the technique of statistical analysis of coordinate distributions of the mean values of the optical anisotropy parameters.